Venous drainage disorder after pulmonary lobectomies - A. L. Akopov; A. S. Agishev; N. S. Yakovleva (Вестник хирургии имени И.И. Грекова)
INTRODUCTION. The venous drainage disorder from the remaining lung after lobectomy is a life–threatening complication. Usually, thrombosis is considered to be the cause of pulmonary vein obstruction, but in some cases, it can be explained by an unintentional intraoperative ligation or crossing of segmental and subsegmental pulmonary veins.METHODS AND MATERIALS. From 2003 to 2022, authors observed 7 patients who had injury of the pulmonary veins of the remaining part of the lung during lobectomies.RESULTS. In all cases, there were anatomy variants of the pulmonary venous bed that were different from the classical one. Cross-section of pulmonary vein of the remaining part of the lung was diagnosed intraoperatively in 2 patients (29 %), and therefore, the volume of the planned resection was expanded. 3 patients were re–operated (43 %, 2 completive pneumonectomies – right- and left-sided, 1 wedge lung resection). Conservative therapy and active observation were performed in 2 patients (29 %). The rate of mortality was 29 % (2 cases).CONCLUSIONS. The knowledge of the most common anatomy variants of the pulmonary venous bed and a certain alertness about the possibility of the development of venous plethora of the remaining lung during surgery and in the postoperative period will prevent or diagnose the complication in time. CT angiography can help with this.